Prevalence, antimicrobial resistance profiling and genetic diversity of Campylobacter jejuni and Campylobacter coli isolated from broilers at slaughter in China. (November 2016) - Han, Xinfeng; Zhu, Dongmei; Lai, Haimei; Zeng, Hang; Zhou, Kang; Zou, Likou; Wu, Congming; Han, Guoquan; Liu, Shuliang
Abstract: A total of 651 samples from broiler cecal samples, carcasses, carcass parts collected at the slaughterhouse level in Sichuan Province of China were examined for the occurrence of Campylobacter jejuni and Campylobacter coli . After confirmed by species-specific multiplex PCR, the recovered isolates were examined for resistance to antimicrobials using an agar dilution method and investigated for the mutation of gyrA, tetO gene and V domain of 23S rRNA as well as the presence of class 1 integron and the associated gene cassettes. In addition, the genotype relatedness of the isolates was determined by pulsed-field gel electrophoresis (PFGE) profiling. The prevalence of Campylobacter was 56.1% in cecal samples, 31.0% in carcasses and 17.0% in carcass parts, respectively. Among them, C . jejuni accounted for 24.6% and C . coli occupied 20.0% of the samples. The strains of C . jejuni were most frequently resistant to ciprofloxacin (88.1%), followed by resistance to tetracycline (79.4%) and levofloxacin (78.1%). Most of the C . coli isolates were resistant to ciprofloxacin (100%), tetracycline (98.5%), levofloxacin (98.5%), clindamycin (98.5%) and erythromycin (93.9%). Antimicrobial resistance profiling showed that 93.7% of campylobacters were multidrug resistant (MDR) strains. Moreover, class 1 integrons were detected in 98.6% of MDR campylobacters, among which 98.7% were positive for C . jejuni and 98.5% for C . coli . Three kinds of gene cassettes-associated amplicons were identified and the amplicons profile of 1000–750–500–250 bp was the predominant pattern linked to the aminoglycoside resistance gene of aadA 2. The presence of mutation in gyrA, tetO and 23S rRNA between C . jejuni and C . coli varied from 89.7% to 97.3%, 96.6% to 94.1%, and 95.0% to 96.7%, respectively. Finally, the results of PFGE indicated that, 33 PFGE profiles were generated among 78 isolates of C . jejuni and the similarity level ranged from 42.1% to 99.1%. By contrast, 15 PFGE patterns were produced among 68 C . coli isolates sharing a similarity level of 54.0%–99.7%. Comparison of the PFGE and antimicrobial resistance profiles of the isolates reflected the high genetic diversity of Campylobacter tested. A poor correlation among the antimicrobial resistance patterns, resistance determinants and PFGE genotypes was observed in C . jejuni . Our study showed that there were several points of cross-contamination during broiler slaughter, and a high diversity of PFGE types in the Campylobacter isolates with high resistances to ciprofloxacin and tetracycline. Highlights: Surveillance of class 1 integrons and linked gene cassettes in Campylobacter jejuni and Campylobacter coli . Mutation of resistance determinants related to clinically relevant antimicrobials. C . coli was more robust in the stress conditions than C . jejuni . C . coli showed higher relatedness than C . jejuni isolates from the slaughter line.